Melawan Academic Fraud: Menguak Peran IPK dan Kejujuran Mahasiswa Akuntansi dalam Fraud Pentagon dengan Dark Triad sebagai Moderasi - Diah Ajeng Rachmawati; Sari Rusmita; Nella Yantiana (Universitas Negeri Padang, 2024)
Fraud is a problem that often occurs and is a worrying issue among society, including in the world of education. The GPA is considered very valuable so that most students indicate fraud in the process of achieving a perfect score. This study investigates the influence of fraud pentagon variables on academic dishonesty behavior among undergraduate accounting students at faculty Economics and Businnes, Tanjungpura University, with dark triad factors as a moderating, while also exploring student prespecyives on GPA and the causes of academic dishonesty. This research focuses on understanding the influence of pressure, opportunity, rationalization, competence, and arrogance, which are combined in the fraud pentagon, contributing to academic fraud behavior with the dark triad: Machiavellianism, narcissism, and psychopathy used as moderation. This research uses quantitative methods with data collected throught survey with the help of Google forms. The data population from the research is undergraduate students in Accounting. Faculty of Economics and Business, Tanjungpura University. This research involved 100 students as respondents and data was processed using SPSS version 26 software. The research result showed that rationalization, competence, and arrogance had a positive effect in influencing academic fraud behaviour, while pressure and opportunity as moderation had a negative effect. The dark triad as moderation is unable to strengthen the variables of opportunity, competence, rationalization and arrogance towards academic fraud behavior.